2014
DOI: 10.2340/16501977-1823
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the modified sphygmomanometer test to assess strength of the lower limbs and trunk muscles after stroke

Abstract: In general, the MST showed adequate criterion-related validity, test-retest and inter-rater reliabilities for the assessment of strength of the lower limb and trunk muscles in subjects with chronic stroke. For the majority of the assessed muscles, only one trial, after familiarization, provided adequate strength values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 37 publications
4
58
1
1
Order By: Relevance
“…All the eight studies, which assessed the strength of the hip extensor muscles, reported the positioning of the subjects and half (50%) (15,21,40,44), adopted the supine position with the hips and knees flexed. The seven studies (15,21,22,32,41,43,44) that assessed the strength of the hip abductor muscles, all adopted the supine position. The only study that assessed the strength of hip adductor muscles (15) adopted the supine position with the hip in neutral in the frontal plane and knees extended.…”
Section: Contraction Time: 5smentioning
confidence: 99%
See 2 more Smart Citations
“…All the eight studies, which assessed the strength of the hip extensor muscles, reported the positioning of the subjects and half (50%) (15,21,40,44), adopted the supine position with the hips and knees flexed. The seven studies (15,21,22,32,41,43,44) that assessed the strength of the hip abductor muscles, all adopted the supine position. The only study that assessed the strength of hip adductor muscles (15) adopted the supine position with the hip in neutral in the frontal plane and knees extended.…”
Section: Contraction Time: 5smentioning
confidence: 99%
“…All muscular groups of the LL assessed with portable dynamometry had some type of reliability investigated. three studies (10%) (11,39,44) reported the use of immediate verbal feedback. The demonstration and familiarization procedures were also rarely reported.…”
Section: Contraction Time: 5smentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the lower limb muscle strength, the modified sphygmomanometer test (MST) 19 was used, which provides objective measurements and has a low price 19,20 . In addition, it also presents adequate measurement properties for post-stroke individuals 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Wherever hypertension is present in low-middle-income countries, the sphygmomanometer should be around, although it has largely been replaced in many high-income countries. The potential of the sphygmomanometer was recently reported in the Journal of Rehabilitation Medicine, showing how a modified sphygmomanometer test could provide an assessment of the strength of the lower limb and trunk muscles in subjects with chronic stroke (15). In hemiplegia, recent studies have indicated that building up of power in the hemiplegic leg is important in leading to significant improvement of function (16,17).…”
mentioning
confidence: 99%